Matrix Metalloproteinases in patients with Multiple Sclerosis. - Rebeca A. Fernández Carriera; Lourdes Fernández Queija; Rosa F. Lara Rodríguez; José Cabrera Gómez; Idalmis Suárez Luis; Mabel María León Ortiz; Sergio González García; Alina González-Quevedo Monteagudo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Fundament: The proteolitic rupture of the extracellular matrix due to metalloproteinase 2 and 9 is one of the aspects that can influence in the alteration of the permeability of the blood-brain barrier (BBB) in multiple sclerosis. Objective: To determine metalloproteinase activity with gelatinous activity in patients suffering from multiple sclerosis. Methods: the cerebrospinal fluid (CSF) samples taken from 31 patients suffering from multiple sclerosis and a control group formed by 21 patients without neurological disease. The metalloproteinase 2 and 9 activities in the cerebrospinal fluid were determined by zimográfica technique through polyacrylamide gel electrophoresis. The bands were later analysed by their molecular weight and the relative metalloproteinase 9 activity was calculated. Total protein concentrations, albumin and immunoglobulin G (IgG), the IgG rate and the Q rate were assessed to evaluate the IgG intrathecal and the functional state of the blood-brain barrier. Results: metalloproteinase 2 activity was detected in the cerebrospinal fluid of all patients and control group. Metalloproteinase 9 activity was only found in the 61.3 % of the patients. The presence of relative metalloproteinase 9 activity was neither associated with the clinical variables nor the laboratory ones. An association was found between its presence and the oligoclonal bands in patients with multiple sclerosis. In those patients under immunomodular treatment it was presented with less frequency. Conclusions: There is a possible participation of Metalloproteinase 9 in the immunopathological mechanisms of the multiple sclerosis.